The Fertility Impacts of Development Programs - Aletheia Donald; Markus Goldstein; Tricia Koroknay-Palicz; Mathilde Sage (Institute of Labor Economics (IZA), 2024)
This paper examines how women's fertility responds to increases in their earnings and household wealth using six experiments conducted in Sub-Saharan Africa. Contrary to predictions that an increase in female earnings raises the opportunity cost of childbearing and that this will lower fertility, we find that an increase in the profits of female business-owners in Ethiopia and Togo results in them having more children. We also observe a positive fertility response to increases in the value of household assets induced by land formalization programs in Benin and Ghana. These results are driven by women who are in most need of sons for support in old age or in the event of widowhood. Our findings suggest that women's lack of long-term economic security is an important driver of fertility in Sub-Saharan Africa.
Keywords: J13; O12; D13; J12; I32; 330; fertility; households; Sub-Saharan Africa